Feeding future generations How finance can boost innovation in agri-food - Executive summary - European Investment Bank (European Investment Bank, 2019)
The food sector is a strategic part of the European economy, but it faces many complex challenges: The sector is afraid of risk Spending on innovation is low The sector does not use technology adequately The financing landscape is too fragmented To prepare food production for the future, we need more innovation, we must reap the full potential of technology, and we need creative financing.